Resonant suppression strategy of impedance remodeling for multi-inverter grid-connected system in weak grid - ZHANG Shicong; XU Yonghai; TAO Shun; YU Yongyue; ZHANG Zhi (电力工程技术)
In weak grid, a multi-inverter grid-connected system may be simultaneously affected by large grid impedance and background harmonics. The interaction between inverter and grid is enhanced by the large grid impedance, resulting in resonance problems. Furthermore, the grid-connected voltage and current waveforms are distorted by the background harmonics, which makes the system unable to meet the grid-connected requirements. In view of this, firstly, an impedance model for multi-inverter grid-connected system is established, and the mechanism behind waveform distortion and resonance in weak grid is clarified. Subsequently, a control strategy combining improved grid voltage feedforward with parallel adaptive active damping is proposed. The improved grid voltage feedforward is used to reshape the impedance of the multi-inverter grid-connected system in order to mitigate background harmonics effects, while the active damper is employed to synthesize virtual resistance for suppressing system-grid resonance. When there are changes in working conditions of the system, the damping effect can be further improved by adaptively adjusting virtual resistance values through compensation. Simulation results show that background harmonics and resonance problems can be effectively suppressed by the proposed strategy, and the adaptability of multi-inverter grid-connected systems in weak grid is enhanced.